The Influence of Internal Marketing on Employee Performance in The Ghanaian Public Sector: The Mediating Role of Organizational Commitment - Osei, Francis; Owusu, Alfred; Kankam-Kwarteng, Collins; Agyemang, Gertrude (UI Scholars Hub, 2023)
This research assessed the influence of internal marketing on employee performance in the public sector of Ghana, as mediated by organizational commitment. This research was conducted on a total of 300 public sector workers in Ghana, of whom 200 responses were received, representing a response rate of 66.6%. Purposive and convenience sampling techniques were adopted. The PLS-SEM technique was implemented to determine the associations among the variables. The research results reveal significant associations among internal marketing, employee performance, and organizational commitment. Moreover, a partial role is played by organizational commitment. The research findings indicate that the public sector, particularly Metropolitan, Municipal, and District Assemblies, should enhance training programs on internal marketing to bridge the knowledge gap between new and old employees. The Metropolitan, Municipal, and District Assemblies in Ghana should implement effective internal marketing practices and policies that increase employee performance for organizational commitment, and the authorities in the public sector, particularly in Metropolitan, Municipal, and District Assemblies, should strategically incorporate internal marketing principles into the organizational culture for organizational performance